Characterization and Application of Chitosan as a Natural Coagulant in Reducing Remazol Red Dyestuff Concentration and COD Value of Batik Liquid Waste - Rifana Adilla Safitri; Maya Rahmayanti (Jurnal Kimia Sains dan Aplikasi, 2020)
Research on chitosan application as a natural coagulant in reducing the concentration of remazol red dye from batik liquid waste has been carried out. This study aims to study the effect of the acidity of batik wastewater on the coagulant ability to reduce the remazol red dye concentration and the COD value of batik liquid waste. In this study, chitosan compounds before and after coagulation were characterized using Fourier Transform Infrared (FTIR) Spectroscopy. The pH range used in the coagulation process was pH 2-6. Post-coagulation chitosan FTIR spectra showed a shift in the wave number in the 3400 cm-1 area, which indicated an interaction between the -OH group of chitosan and the dye remazol red. Remazol red dye was maximally coagulated by chitosan at pH 2. The percentage reduction in the dye concentration reached 100%, and the decrease in COD value at that pH was 71.69%.